Role of life events and personality in alcohol dependent individuals: a study - Preeti Gudlavallety; Sumaiya Saleem Ahmed; Pragathi Gollepally (Advances in Medical, Pharmaceutical and Dental Research, 2023)
Introduction: Over 2 billion people worldwide, and 14.6% of India’s population consumes alcohol, 18.5% of whom are dependent.95% of alcohol users are males, with 74% falling in the age bracket of 18-49 years. Stressful life events and personality may act as important determinants in persistence of alcohol use, hence influencing long term treatment of alcohol dependent individuals. This study focuses on these aspects to fill in the dearth of research on this concept over the past decade. Methodology: A case control study was done at a tertiary care hospital with 80 literate male participants; 40 cases meeting the criteria for alcohol dependence as per ICD 10, and 40 age matched controls with no history of alcohol consumption. Participants were screened with General Health Questionnaire-12 to exclude other illnesses. All participants were administered sociodemographic proformas, Presumptive Stressful Life Events Scale, Eysenck Personality Questionnaire - Revised,.   Results: Sociodemographic profiles of cases and controls were similar. Mean number of life events and undesirable life events were higher among cases, and mean number of desirable life events were higher among controls. Cases displayed higher scores in the domains of psychoticism, neuroticism and extraversion.  Conclusion: Alcohol dependent individuals differ significantly from life time abstinent individuals on personality variables and had experienced more subjective distress. A holistic approach addressing coping strategies, personality development, and education about substance use among adolescents would aid in individual and social well being. Received: 17 January 2023 Accepted: 18 March 2023 Published: 11 April 2023